2018
DOI: 10.1155/2018/8645709
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Lane-Changing Behavior in Freeway Off-Ramp Areas from the Shanghai Naturalistic Driving Study

Abstract: The objective of this study is to investigate lane-changing characteristics in freeway off-ramp areas using Shanghai Naturalistic Driving Study (SH-NDS) data, considering a four-lane freeway stretch in various traffic conditions. In SH-NDS, the behavior of drivers is observed unobtrusively in a natural setting for a long period of time. We identified 433 lane-changing events with valid time series data from the whole dataset. Based on the logit model developed to analyze the choice of target lanes, a likelihoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…The lane-change position of normal drivers was mainly concentrated within around the first 60% of the weaving length, while the lane-change position of aggressive drivers was mainly concentrated around the first 70% of the weaving length. This result indicated that lane-changing to the auxiliary lane is performed by diverging vehicles sufficiently far before the beginning of the merge marking, which is in line with previous research [43]. With respect to the duration of lane changes, it is obvious that the conservative drivers had the largest range of duration time for the three kinds of weaving length, followed by normal drivers and aggressive drivers.…”
Section: Lane Change Position and Durationsupporting
confidence: 89%
“…The lane-change position of normal drivers was mainly concentrated within around the first 60% of the weaving length, while the lane-change position of aggressive drivers was mainly concentrated around the first 70% of the weaving length. This result indicated that lane-changing to the auxiliary lane is performed by diverging vehicles sufficiently far before the beginning of the merge marking, which is in line with previous research [43]. With respect to the duration of lane changes, it is obvious that the conservative drivers had the largest range of duration time for the three kinds of weaving length, followed by normal drivers and aggressive drivers.…”
Section: Lane Change Position and Durationsupporting
confidence: 89%
“…In Germany, the first exit sign is positioned at about 2,000 m upstream of an off-ramp, which is similar to China. According to Zhang et al ( 51 ), 85% of the vehicles pre-allocate after 1,200 m upstream of an off-ramp. In fact, only one vehicle pre-allocated before 2,000 m upstream of an off-ramp.…”
Section: Data Preparationmentioning
confidence: 99%
“…According to United States Department of Transportation [6], the proportion of fatal crashes on freeways is significantly higher than that on other road types. Further, on-ramp areas of freeways may be prone to relatively more traffic crashes than other sections of freeways (Cheng et al, 2017) [7] because drivers have been facing a high competition for merging space in such areas [8,9]. In this regard, capable solutions need to be sought in order to proactively assess or predict on-ramp crash.…”
Section: Introductionmentioning
confidence: 99%